Factors affecting unmet need for family planning in Eastern Sudan - Ali Abdel Aziem A; Okud Amira (BMC, 2013)
Abstract Background In the developing countries millions of women in the reproductive age who don't use contraceptives prefer to postpone or limit their birth. This indicates their failure to take necessary decision to prevent and avoid unwanted pregnancy. Methods A community-based cross sectional household survey was conducted to investigate unmet need for family planning and associated factors and total demand for family planning in Kassala, Eastern Sudan between 1st May and 31st July 2012. Results A total of 812 married women were enrolled in this study. Their mean age and parity was 31.8 (7.3) and 3.4 (1.8) respectively. Ever use of contraception was 25.4% (206/812) and 26.2% (213/812) were currently using contraception. Unmet need for spacing was 15.1% while unmet need for limiting was 0.7%. The pregnant and amenorrheic women whose the pregnancy or birth was unwanted and mistimed were 105 (13%) and 130 (16%) respectively. Using Westoff model the total unmet need was estimated as 44.8%. The total demand for family planning was 71%. In logistic regression model, while age, age at marriage, parity, residence and experience of child death were not associated with total unmet need for family planning, women education < secondary level (OR=7.8; CI=5.6-10.9; P=0.00), husband education < secondary level (OR=1.9; CI=1.3-2.6, P = 0.00) and woman's occupation; housewife (OR=4.3; CI=2.5-7.2; P=0.00) were associated with the total unmet need. Conclusions Unmet need for family planning in Eastern Sudan was significantly higher among women with less than secondary education. Also; it is influenced by couple's educational status and woman's occupation. The results of this study necessitate the need for the programme managers to take into account the concept of reproductive health education.